Engagement of atrial fibrillation patients with the AF-EduApp, a new mobile application to support AF management - Knaepen, Lieselotte; Delesie, Michiel; Theunis, Rik; Gorissen, Peter; Vijgen, Johan; Dendale, Paul; Desteghe, Lien; Heidbuchel, Hein (Frontiers in Cardiovascular Medicine, 2023)
Introduction: A multidisciplinary approach is needed for the management of atrial fibrillation (AF) in which the patient has a central role. Smart devices create opportunities to improve AF management. This paper aimed to evaluate the in-house developed AF-EduApp application on its usability, satisfaction, and communication effectiveness with the care team. Methods: During a multicenter, prospective randomized controlled trial, 153 AF patients used the AF-EduApp for 12-15 months. The AF-EduApp contains six main modules: Questionnaires, Education, Measurement data entry, Medication overview with reminders, Appointments, and Communication with the care team. The App focuses on four main goals: (1)to improve AF knowledge, (2)to increase self-care capabilities, (3)electronic monitoring to improve therapy adherence to oral anticoagulation (OAC), and (4) communication with the care team. Patients unable to use the AF-EduApp were assigned to a no-App control group (n=41)without intervention comparable to the standard care group(SC, n=346) of the AF-EduCare study. Results: A total of 152 patients used the App during a mean follow-up of 386.8±108.1 days. They opened the application on average on 130.1±144.7 days. Of the 109 patients still in follow-up at 12 months, 90 patients(82.6%) actively used the application at least one day in the next 41 days. The Measurement module was the most used, with a median of used days over the total available days of 6.4%. A total of 75 App patients(49.3%) asked questions, mostly clinical-related questions (e.g. medication use, or actionability on clinical entered parameters). A mean score of 8.1±1.7 about the ‘perceived quality of follow-up in the past year’ was given by the App ITT patients, which was slightly higher compared to with a trend toward a significant difference with the SC group( 7.±2.0; P=.072).Patients who used the App were more attracted to future follow-up with an application compared to patients who would be capable of using the application of the SC group(31.6% vs. 12.5%; P<.001). Conclusion: This study showed a positive attitude towards using a mobile application, with AF patients using the application one-third of the available days. Patients used the App most for entering measured parameters, and to contact the care team.